Decomposing the net efficiency of Active Labor Market Programs - Dominik Sliwicki (Institute of Economic Research (IER), 2015)
Each state intervention in the labor market must be evaluated at the end in terms of efficiency. It is especially important during periods when the resources allocated for this purpose are limited. The most commonway to verify it, is to estimate the gross efficiency. The gross efficiency is the percentage of unemployed who moved to employment following the end of the program. Gross efficiency indicators contain a number of apparent effects that distort the effect of intervention. Therefore we estimate net efficiency indicators, which reflects the actual effect of state intervention in the labor market. The aim of this paper is to estimate the net efficiency indicator of active labor market programs using the Oaxaca-Blinder decomposition. Analysis will be carried out using data sets of unemployed participating and not participating in active labor market programs.
Keywords: C21; C25; J68; 330; Oaxaca-Blinder decomposition; net efficiency of active labor program